First Lorenzo M. Tanada CHIMES award - Salazar, Godofredo (Animo Repository, 2002)
The System CHIMES Award Committee (SCAC) announced the winners of the first Lorenzo M. Tanada CHIMES AWARD. College of Engineering faculty member Engr. Godofredo Salazar, won the special award. He shared the honor with Dr. Jose Esteban of the DLSU-Health Sciences Campus. The awarding ceremony was on May 28. It was also the death anniversary of Senator Lorenzo Tanada.